Self-Efficacy, Self-Love, and Fear of Compassion Mediate the Effect of Attachment Styles on Life Satisfaction: A Serial Mediation Analysis - Deniz, Mehmet Engin; Kurtulus, Hacer Yildirim (SAGE PUBLICATIONS INC, 2025)
This study examined the effect of attachment styles on the life satisfaction of adults and the serial mediating effect of self-efficacy, self-love, and fear of compassion in this effect for the first time in the literature to the best of our knowledge. The study group consisted of a total of 639 adults. As a result of the study, it is seen that secure attachment affects life satisfaction positively. This process is mediated by the variables of high self-efficacy, high self-love, and low fear of compassion. However, avoidant attachment seems to negatively affect life satisfaction. This process is mediated by low self-efficacy, low self-love, and high fear of compassion variables. Apart from these results, it was observed that anxious-ambivalent attachment negatively affected life satisfaction, but this relationship was not mediated by self-efficacy, self-love, and fear of compassion. This result may be due to the fact that people with anxious-ambivalent attachment style perceive others positively despite seeing themselves as worthless and inadequate. These people may not want to show compassion for themselves because they have low self-worth, but they may show compassion for others because they find them valuable.
Keywords: Attachment styles; self-efficacy; self-love; fear of compassion; life satisfaction; Psychology